PENINGKATAN PRESTASI BELAJARDENGAN COMPUTER AIDED DRAWING (CAD) SEBAGAI MEDIAPEMBELAJARAN BERBASIS KASUS - Floriberta Binarti (Jurnal Kependidikan, 2005)
Abstract Rapid development of information technology offers computer as an interesting teaching tool. This study of investigated the effectiveness of Computer Aided Drawing (CAD) as a teaching media of “Struktur dan Konstruksi Bangunan Gedung 1” in School of Architecture at UAJY. Case based pre-test and post-test are the research instruments. They are used to measure the improvement of student’s competence in applying structural principles with the structural design of a one story building in respect to the using of CAD as a teaching media. Both thesis were conducted four times, each before and after presentation of the subject matter using CAD.T test shows significant improvement of student’s learning achievement due to the use of CAD as a teaching media. Some facilities in CAD could help students to understand the position and the relation of structural elements by presenting them in 2 dimensions and 3 dimensions simultaneously in district colors, which are not available in conventional media. Keywords: Computer Aided Drawing (CAD), case based learning, learning achievement